2021
DOI: 10.1016/j.eclinm.2021.100985
|View full text |Cite
|
Sign up to set email alerts
|

Global breast cancer incidence and mortality trends by region, age-groups, and fertility patterns

Abstract: Background: Breast cancer (BC) has been increasing globally, though it is unclear whether the increases are seen across all age groups and regions and whether changes in rates can be primarily attributed to decreasing fertility rates. We investigated age-specific trends in BC incidence and mortality from 1990 to 2017, worldwide and by region, and evaluated whether incidence trends are explained by decreases in fertility. Methods: We used country-level data to examine trends in BC incidence and mortality rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 34 publications
1
92
0
1
Order By: Relevance
“…In light of current epidemiological trends, i.e., an increase in breast cancer morbidity, especially among women aged <50 years, this type of cancer poses an important public health problem [ 1 , 2 ]. Cancer mortality constitutes a significant burden for healthcare systems worldwide [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of current epidemiological trends, i.e., an increase in breast cancer morbidity, especially among women aged <50 years, this type of cancer poses an important public health problem [ 1 , 2 ]. Cancer mortality constitutes a significant burden for healthcare systems worldwide [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence rates for breast cancer are particularly high in developed countries, whereas mortality rates are higher in developing countries [ 1 ]. Recent years have seen a statistically significant increase in breast cancer incidence in women under 50 years who lead an active professional and family life [ 2 , 3 ]. At the same time, as a result of screening programs and evermore effective treatment methods, the prognosis for patients diagnosed with malignant breast cancer has considerably improved, and their 5-year survival rate has increased [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, incidence rates of breast cancer are rising fast in transitioning countries. According to Lima SM et al, Middle East North Africa had the largest per-year increase in overall incidence between1990 and 2017 (APC = 2.38, 95% CI = 2.29, 2.47) [ 25 ]. Sung H et al reported that some of the most rapid increases are occurring in sub-Saharan Africa with an increase rate >5% per year in Malawi (Blantyre), Nigeria (Ibadan), and the Seychelles and of 3% to 4% per year in South Africa between the mid-1990s and the mid-2010s.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC) is the most prevalent malignancy in women worldwide, with incidence increasing in last decades (1). Oppositely, mortality from BC decreased in last years, due to the significant advancements in screening programs and therapeutical interventions (2). In response to the progressive increase of women living after a diagnosis of BC, survivorship issues related to cancer treatment and its impact on bone health and health-related quality of life (HRQoL) have progressively emerged (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%